The Relation Between Non-Carious Cervical Lesions and Possible Etiological Factors – A Study from a Tertiary Care Setting of Pakistan - Alam, Mafaza; Shah, Syed Muzammil Hussain; Alam, Laima; Shah, Pir Jawad Ali; Bibi, Afshan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To investigate and compare the risk factors of Non carious cervical lesions in relation to demographics, dietary, social and hygiene maintaining habits in Pakistani population presenting to Armed Forces Institute of Dentistry Rawalpindi. Study Design: Cross sectional analytical study. Place and Duration of Study: Department of Operative Dentistry, Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from Dec 2018 to May 2019. Methodology: Two hundred patients of both genders ranging from age 12 to 70 years with a mean age of 46.4 ± 12.4 were studied for Non carious cervical lesions presence on convenience sampling technique. Questionnaires regarding their diet, acidic food consumption, social habits, frequency and pattern of brushing were being filled. Chi square statistics were used to compare groups and results were noted. Results: Old age (55.4 ± 0.8 years), vegetarian diet (p≤0.001), consumption of acid foods (p≤0.001), bruxism (p≤0.001), harder tooth brushes (p≤0.001) with variable movements (p≤0.001) showed higher incidence of non-carious cervical lesions. Whereas use of fluoridated toothpastes (p≤0.001) and xylitol gums (p=0.02) demonstrated protection against the occurrence of these lesions. Conclusion: The presence of Non carious cervical lesions was linked with the use of harder toothbrushes, variable vigorous pattern for tooth brushing, consumption of a vegetarian diet, and greater consumption of acidic food and bruxism. Effective policies should be developed for oral health and awareness of such conditions.